Desain dan Uji Coba Media Pembelajaran Berorientasi Everyday Life Phenomena pada Materi Termokimia - Putra Siagian, Dolok; Yasthophi, Arif (LPPM Universitas Negeri Jakarta, 2021)
This research was instigated by the lack of media that can facilitating teachers in explaining learning material, and the media that could be used frequently although outside lesson hours. This research aimed at designing everyday life phenomena-oriented learning video on Thermochemistry lesson by using Wondershare Filmora software, and it should be valid based on the validation by the experts of material and media, teacher and student practicality test. It was R&D (Research and Development) with Borg and Gall development model, and the steps were (1) researching and collecting information, (2) planning, (3) developing the initial form of the product, and 4) testing the practicality and student response, and (5) revising the product. Preliminary field testing was conducted to the twelfth-grade students of MIPA 1 at State Senior High School 2 Tambang. The score of validation by the experts of media and material was 86.25% with very valid criterion. The score of teacher practicality test was 92.5% with very practical category, and the score of student practicality test was 84.20% with very practical category. Keywords: Learning Video, Wondershare Filmora, Everyday Life Phenomena, Thermochemistry